Payment Banks vs. Traditional Banking in India: A Comparative Analysis (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The Indian banking sector has witnessed a significant structural evolution with the introduction of Payment Banks (PBs) in 2015, following the recommendations of the Nachiket Mor Committee. Conceived as differentiated banks, PBs aim to advance financial inclusion by targeting unbanked and underbanked populations through technology-driven, low-cost models. This stands in contrast to Traditional Banks (TBs), which operate as universal banks offering a full spectrum of financial services, including credit, and cater to a broad customer base. While both models coexist within the same regulatory environment, their objectives, operational frameworks, and market strategies differ substantially. This study provides a comprehensive comparative analysis of Payment Banks and Traditional Banks in India, evaluating their respective business models, performance, customer reach, and impact on financial inclusion. It aims to identify key areas of competition and collaboration and assess the long-term viability and synergistic potential of both models.